Evaluating Conditions of Outsourced Pharmacies in Teaching Hospitals of Alborz University of Medical Sciences: A Cross-Sectional Study - Roya Rajaee; Sima Marzban; Ehsan Zarei (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Outsourcing is the strategy of reducing expenses and improving organizational quality whose evaluation in healthcare organizations is of special importance. This study aims to investigate the status of outsourced pharmacies of Alborz University of Medical Sciences based on personnel perspectives and available documentation. Methods: This was a descriptive analytical and cross-sectional study conducted in outsourced pharmacies of 10 teaching hospitals of Alborz University of Medical Sciences. Expenses, revenues and working time were derived from the hospitals' information centers and the documents. 128 relevant officials were selected by census to investigate the views of managers and authorities of clinical wards on outsourcing. Authors analyzed data using descriptive statistics, t-test and chi-square test through SPSS22 software. All cost was converted to US dollar by using the average exchange rate in 2019 (1USD=110.000IR). Results: The average satisfaction of managers and staff with outsourcing pharmacies were 4.20 (82 %) and 4.45 (80 %) out of 5. The highest level belonged to medicine expiration date with the average of 4.64, and the lowest score was related to medicinal status at the time of delivery with the average of 4. Consumption expenses for a bed in outsourced pharmacies regarding all the hospitals were 123 $, and the profitability of the pharmacy for one bed was134 $ (5.540.900 Riyals). Conclusion: Based on the results, the following components had a relatively proper quality and an acceptable quality in all the respects of the staff's view regarding the conditions in the pharmacies. They can be inferred as the most salient characteristics of the present study in investigating the quality of outsourcing the pharmacies of the teaching hospitals in Alborz medical sciences. The important components include: The time spent by executive managers of the pharmacy's affairs, decrease of the manager's workload, improvement of management, increase in management's satisfaction in the organization and etc.